Statistical analysis of 1000 ulcus gastrectomies performed at the Hospital de Clínicas - Matteucci, Pablo (Cirugía del Uruguay, 1974)
The paper compares results of Billroth II Gastrectomies for ulcus due in which total or partial anastomosis was performed. Case material consists of 1000 patients operated between 1954 and 1969 in the Hospital de Clínicas (University Hospital) of Montevideo. Post-operatory gastric retention, complications and re-operations are discussed. Results point to Hoffmaister- Finsterer type gastrectomy as the most favourable,